GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGELOLA SMP NEGERI 2 RAMBATAN - Nofri Ade Siska (IAIN Batusangkar, 2016)
This research was purposed at describing the leadership style of headmaster in Secondary School 2 Rambatan. This research used qualitative paradigm by applying case study method. In collecting the data the researcher used tape recorder, interview guideline and observation sheet and applied the techniques of interview, observation and documentary study. The informants of this research were 28 persons which consist of headmaster, the teacher and the administration staff of Secondary School 2 Rambatan. The results of the research obtained that (1) in managing teachers’ competence the headmaster applied strict style and strongly discipline; (2) In motivating teachers’ to improve the students’ achievement the headmaster applied democratic style; (3) In developing curriculum the headmaster applied democratic style; and (4) in managing financial resources the headmaster applied strict style, democratic, and participative. Keywords: Leadership Style, Headmaster, Secondary School, Rambatan